miR-33b-3p Acts as a Tumor Suppressor by Targeting DOCK4 in Prostate Cancer - Mei, Yu; Li, Kai; Zhang, Zhicheng; Li, Mengmeng; Yang, Hong; Wang, Hui; Huang, Xuemei; Li, Xinyuan; Shi, Shuhua; Yang, Huanjie (Frontiers in Oncology, 2021)
Despite that androgen-deprivation therapy results in long-lasting responses, the disease inevitably progresses to metastatic castration-resistant prostate cancer. In this study, we identified miR-33b-3p as a tumor suppressor in prostate cancer. miR-33b-3p was significantly reduced in prostate cancer tissues, and the low expression of miR-33b-3p was correlated with poor overall survival of prostate cancer patients. Overexpression of miR-33b-3p inhibited both migration and invasion of highly metastatic prostate cancer cells whereas inhibition of miR-33b-3p promoted those processes in lowly metastatic cells. The in vivo results demonstrate that miR-33b-3p suppresses metastasis of tail vein inoculated prostate cancer cells to lung and lymph nodes in mice. DOCK4 was validated as the direct target of miR-33b-3p. miR-33b-3p decreased the expression of DOCK4 and restoration of DOCK4 could rescue miR-33b-3p inhibition on cell migration and invasion. Moreover, downregulation of miR-33b-3p was induced by bortezomib, the clinically used proteasome inhibitor, and overexpression of miR-33b-3p enhanced the insufficient inhibition of bortezomib on migration and invasion as well as metastasis of prostate cancer cells. In summary, our findings demonstrate that miR-33b-3p suppresses metastasis by targeting DOCK4 in prostate cancer. Our results suggest that enhancing miR-33b-3p expression may provide a promising therapeutic strategy for overcoming that proteasome inhibitor’s poor efficacy against metastatic prostate cancer.